A single nucleotide polymorphism (−250 A/C) of the GFAP gene is associated with brain structures and cerebral blood flow. Issue 1 (16th October 2019) - Takahashi, Yuta; Takeuchi, Hikaru; Sakai, Mai; Yu, Zhiqian; Kikuchi, Yoshie; Ito, Fumiaki; Matsuoka, Hiroo; Tanabe, Osamu; Yasuda, Jun; Taki, Yasuyuki; Kawashima, Ryuta; Tomita, Hiroaki
Abstract : Aim: Glial fibrillary acidic protein (GFAP), the intermediate filament protein expressed in astrocytes, plays a key role in many aspects of brain function through communication with neurons or blood vessels. A common single nucleotide polymorphism (SNP), GFAP –250 C/A (rs2070935), is associated with the transcriptional regulation of GFAP, which can potentially result in the genotype‐specific brain structure. This study aimed to verify the biological effects of the GFAP variants on brain structure and function. Methods: We investigated the associations between the GFAP variants and magnetic resonance imaging findings, including gray and white matter volumes, white matter integrity, and resting arterial blood flow, from 1212 healthy Japanese subjects. Results: The GFAP –250 C/A genotype was significantly associated with total gray matter volume, total white matter volume, average mean diffusivity, and mean cerebral blood flow. In voxel‐by‐voxel analyses, the GFAP genotype showed significant associations with the regional gray and white matter volumes in the inferior frontal lobe and corpus callosum, the regional mean diffusivity in the left posterior region, and the regional cerebral blood flow throughout the brain. Conclusion: This study revealed a common SNP that is significantly associated with multiple global brain structure parameters.